(untitled) (Research, Society and Development, 2023)
Amputations take place when it is necessary to remove a part of a person’s body. It is a long process that impacts directly on the life of the individual. The psychologist can aid in this process, providing follow up and using the tools acquired in their education to be of assistance in the conflicts experienced, helping minimize suffering. This study attempted to identify the role of psychology in the amputation process from the perspective of amputees. This is a qualitative, cross-sectional research with ten voluntary participants who went through an amputation process and, at time of data collection, had participated of a rehabilitation for amputees in a private institution in the city of São Paulo, SP. The instruments used for data collection were a questionnaire and a semistructured interview script, both elaborated by the researchers. Data were analyzed according with the Content Analysis technique by Bardin. Some participants reported that they were visited by the hospital psychologist during hospitalization immediately after the amputation, but none received psychological or psychotherapeutic follow up. It can be inferred that participants were not interested in seeking psychological care after amputation due to their experience or to their lack of contact with hospital psychologists during hospitalization.